Pembuatan Polikristal CuGaSe2 dan Penentuan Konstanta Kisinya - Irmansyah Irmansyah; A. Harsono Supardjo; Arya Rezavidi (Indonesian Journal of Physics, 2002)
Copper Galium Diselenide (CuGaSe2) Polycrystal was synthesized from a stoichiometric mixtures of the elements by using Bridgman Horizontal furnace single zoned. Ingot is visually solid and it did not attach on the ampoule walls. X-Ray Diffraction measurements show that the spectra are the Chalcopyrite peaks. The calculated lattice parameters obtained from Cohen Method are a=b= 5.613 Å , c = 11.014 Å and the ratio c/a =1.962